Common data elements for preclinical epilepsy research: Standards for data collection and reporting. A TASK3 report of the AES/ILAE Translational Task Force of the ILAE. (6th November 2017) - Harte‐Hargrove, Lauren C.; French, Jacqueline A.; Pitkänen, Asla; Galanopoulou, Aristea S.; Whittemore, Vicky; Scharfman, Helen E.
Summary: The major objective of preclinical translational epilepsy research is to advance laboratory findings toward clinical application by testing potential treatments in animal models of seizures and epilepsy. Recently there has been a focus on the failure of preclinical discoveries to translate reliably, or even to be reproduced in different laboratories. One potential cause is a lack of standardization in preclinical data collection. The resulting difficulties in comparing data across studies have led to high cost and missed opportunity, which in turn impede clinical trials and advances in medical care. Preclinical epilepsy research has successfully brought numerous antiseizure treatments into the clinical practice, yet the unmet clinical needs have prompted the reconsideration of research strategies to optimize epilepsy therapy development. In the field of clinical epilepsy there have been successful steps to improve such problems, such as generation of common data elements (CDEs) and case report forms (CRFs and standards of data collection and reporting) by a team of leaders in the field. Therefore, the Translational Task Force was appointed by the International League Against Epilepsy (ILAE) and the American Epilepsy Society (AES), in partnership with the National Institute of Neurological Disorders and Stroke (NINDS) and the National Institutes of Health (NIH) to define CDEs for animal epilepsy research studies and prepare guidelines for data collection and experimental procedures. If adopted, the preclinical CDEs could facilitate collaborative epilepsy research, comparisons of data across different laboratories, and promote rigor, transparency, and impact, particularly in therapy development.